Contraception and abortion in the early Roman Empire: A critical examination of ancient sources and modern interpretations. - Dowsing, Susan. (University of Ottawa (Canada), 2000)
The primary sources contain substantial evidence that contraception and abortion were common methods of birth control during the early Roman Empire. The medical, legal, and literary source texts support the notion that chemical means were most often resorted to. An analysis of the modern scholarship on the topic does not necessarily reflect this. Contrary to the opinions of earlier scholars, modern research has revealed that many of the contraceptives and abortifacients used by the Romans were efficacious. Despite this, the belief persists that dangerous surgical procedures were commonly used as a method of birth control. A reevaluation of these texts in conjunction with other source material has lead to conclusions that are not in accord with those contained in the prevailing modern scholarship.
Keywords: History, Ancient.